ChemInform Abstract: Rhodium‐Catalyzed C—H Activation of Hydrazines Leads to Isoquinolones with Tunable Aggregation‐Induced Emission Properties. Issue 3 (29th December 2015) - Yu, Bole; Chen, Ying; Hong, Mei; Duan, Pingping; Gan, Shifeng; Chao, Hui; Zhao, Zujin; Zhao, Jing
Abstract: A variety of isoquinolones (III) and (V) is readily obtained by a Rh‐catalyzed reaction of benzoylhydrazines with the corresponding alkynes (II) and (IV), respectively.